Orizzonti fenomenologici: animale, mondo, io puro, storia - Failla, Mariannina (B@belonline, 2020)
Preferring the word ‘horizon’ is focusing readers’ attention on the vision of phenomenology as a method at the same time recursive and productive. The issue collects the results of the efforts of a new generation of researchers, gathered for some years around two research experiences located in different times and spaces, but united by a healthy and rigorous experimental approach, i.e. the collective translation of the first part of Husserliana XLII, Grenzprobleme der Phänomenologie. Analysen des Unbewusstseins und der Instinkte. Metaphysik. Späte Ethik (Texte aus dem Nachlass 1908-1937) and the establishment of the International Research Summer School on Genetic Phenomäenology held at the Institute for Philosophy and Sociology of the Polish Academy of Sciences in Warsaw as part of the International Network Genetic Phenomenology and the Human Science.